Rural telemedicine networks using store-and-forward voice-over-ip - Scholl, Jeremiah; Lindgren, Anders; Lambrinos, Lambros (My University, 2009)
Store and forward Voice-over-IP is a suggested solution for supporting Telemedicine at rural health clinics in developing countries. Solutions described to date are designed to support communication by establishing point-to-point connectivity between two sites. In this paper we present an approach for creating scalable Telemedicine networks based on Delay Tolerant Networking. This holds potential for allowing Telemedicine networks to be created that can enable sharing of Teleconsultation and other medical information among a large number of locations in areas that cannot be served by existing solutions.
Keywords: Telemedicine; Automatic speech recognition; Methodology; Communication